Multiple Internal Rates of Return and Decision Criteria Among Mutually Exclusive and Independent Projects - Basnet, Ganesh Bahadur (NUTA Journal, 2021)
This paper focuses on solving methods of unique and multiple internal rates of return of the series of cash flow when net present value is equal to zero, and decision criteria of accepting the independent project. When a project's cash flow has only two sign variations, the internal rate of return (IRR) rule is simple and for analysis, the case with an investment’s cash flows with three or more sign variations to have multiple solutions. The study, also, discussed selecting the best one among mutually exclusive projects on the basis of incremental internal rate of return (IRR) analysis. In the case of mutually exclusive projects, selecting projects based on the minimum attractive rate of return (MARR), accept a pure investment opportunity if IRR ≥ MARR, otherwise reject and accept a pure borrowing opportunity if IRR ≤ MARR, otherwise reject. In practice, the internal rate of return is a popular rule for the project accept/reject decisions.